2020
DOI: 10.1097/nne.0000000000000966
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Dedicated Education Unit Experience on Critical Thinking Development in Nursing Students

Abstract: Aim: The purpose of this study was to identify the impact of the dedicated education unit (DEU) on nursing students' critical thinking ability. Background: The DEU is an innovative approach to clinical education, which uses clinical nurses with expert practice consistently in a competency-based experience. Method: Participants (intervention and control groups) completed the Nursing Executive Center's Critical Thinking Diagnostic Assessment tool before and after clinical experience. Results: Participants includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…On this note, it was found in the literature that the Dedicated Education Unit model is a compelling and well-supported alternative to conventional clinical education. The viability of the DEU model as a clinical education option, which is comparable to traditional models, was demonstrated to key stakeholders using evidence from the literature (Bittner et al, 2021;Lapinski & Ciurzynski, 2020;Rusche et al, 2018). Furthermore, it was shown that implementing the DEU model does not jeopardize nursing program outcomes, such as licensing exam pass rates (Flott et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On this note, it was found in the literature that the Dedicated Education Unit model is a compelling and well-supported alternative to conventional clinical education. The viability of the DEU model as a clinical education option, which is comparable to traditional models, was demonstrated to key stakeholders using evidence from the literature (Bittner et al, 2021;Lapinski & Ciurzynski, 2020;Rusche et al, 2018). Furthermore, it was shown that implementing the DEU model does not jeopardize nursing program outcomes, such as licensing exam pass rates (Flott et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has brought unprecedented challenges to nursing education in the Philippines, disrupting traditional clinical training methods and necessitating innovative approaches to support students' self-efficacy-the belief in one's ability to perform specific tasks and achieve desired outcomes (Bittner et al, 2021). In this context, the Dedicated Education Unit (DEU) model emerges as a promising strategy to enhance the self-efficacy of Filipino nursing students' post-pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, DEU provides a conducive, supportive environment for peer learning, alleviating stress and anxiety (Carey et al, 2018) while significantly increasing critical thinking skills in the learner (Bittner et al, 2021). Lastly, the preceptors in DEUs served as mentors, validators of competencies, and a promoter of critical thinking (Glynn et al, 2017).…”
Section: Anccmentioning
confidence: 99%